Treatment and prognostic factors in primary peritoneal carcinoma: A multicenter study of the anatolian society of medical oncology (ASMO) - (:unkn) unknown (S. Karger AG, 2014)
Background: In this study, we aimed to evaluate the clinicopathological characteristics and prognosis of patients with primary peritoneal carcinoma (PPC), and the effectiveness and toxicity of first-line platinum/taxane combination therapy. Patients and Methods: We retrospectively evaluated 79 patients with PPC, who were treated and followed up between December 2001 and August 2012 at 10 medical oncology clinics. Results: All patients were female, with a median age of 63 years (range 34-79 years). Histopathological diagnoses included primary peritoneal serous carcinoma (PPSC) (n = 69) and mixed epithelial carcinoma of the peritoneum (MEC) (n = 10). Patients received first-line treatment with carboplatin/paclitaxel (n = 67) or cisplatin/paclitaxel (n = 12) combination therapy. Overall response rate, median progression-free survival, and median survival time in the paclitaxel/ carboplatin group and the paclitaxel/cisplatin group were 74.6 vs. 75%, 15.6 vs. 37.8 months, and 41 vs. 70.3 months, respectively. In multivariate analysis, favorable prognostic factors were: ECOG performance status 0 (p < 0.001) and optimal cytoreduction (p = 0.03). Conclusion: PPC is a rare, heterogeneous disease. ECOG performance status and optimal cytoreduction are important prognostic factors regarding survival rates. Platinum/taxane combination therapy is an effective and tolerable regimen in this patient group. © 2014 S. Karger GmbH, Freiburg.
Keywords: Carboplatin; Chemotherapy; Paclitaxel; Prognostic factor